Antitumour effects of Liporaxel (oral paclitaxel) for canine melanoma in a mouse xenograft model. (21st October 2019) - Yang, Ji‐In; Jin, Bohwan; Kim, Su‐Yeon; Li, Qiang; Nam, Aryung; Ryu, Min‐Ok; Lee, Won Woo; Son, Min‐Hee; Park, Hye‐Jin; Song, Woo‐Jin; Youn, Hwa‐Young
Abstract: Paclitaxel, a member of the taxane family, exhibits antitumour effects by targeting the microtubules in cancer cells. Recently, oral paclitaxel has been developed to overcome the side effects of intravenous paclitaxel administration in human patients. The objective of this study was to investigate the antitumour effects of oral paclitaxel in vitro and in vivo. Three weeks after inoculation, oral paclitaxel (25 and 50 mg/kg) or saline was administered every week for three consecutive weeks. To explore the underlying mechanism, tumour angiogenesis was examined by immunohistochemistry with an anti‐CD31 antibody. Tumour cell apoptosis was detected by Terminal deoxynucleotidyl transferase dUTP Nick‐End Labeling assay, and cell cycle arrest was confirmed by western blot analysis. Oral paclitaxel treatment of canine melanoma cells exerted mediated antiproliferative effects and mediated cell cycle arrest in vitro. In animal experiments, after oral paclitaxel administration, the average tumour size decreased to approximately 30% of that in the control. Histologically, oral paclitaxel showed anti‐angiogenic effects and induced the apoptosis in tumour tissues. Oral paclitaxel also downregulated the intratumoural expression of cyclin D1 and inhibited cell proliferation. The study findings support potential application of oral paclitaxel as a novel chemotherapeutic strategy to treat canine melanoma. This is the first study to investigate the potential of oral paclitaxel as a therapeutic drug against canine tumours.